Lokal handeln - systemweit denken: Beschäftigungs-, Qualifizierungs- und Beteiligungspotentiale von Umweltmanagementsystemen in kleinen und mittleren Unternehmen. Zukunftsfähiges Unternehmen (3) - Holger Rohn; Herbert Klemisch; Jörg Giesen; Christa Liedtke (Wuppertal Institut für Klima, Umwelt, Energie, 1998)
– So far EMAS research has shown that the success of environmental management system depends heavily on the participation and qualification of employees on all level in a company, not just on the management level, to reach the proposed goals towards continuous environment improvement. Today most of the companies who have passed the EMAS requirements are still uncertain in how to involve in all level and areas of a company multiplicator and actors: from the trainee, educated and uneducated collaborator, fellow to the master, technician, head of the department to the top management. Therefore it is mandatory to develop an understanding oftheir role and responsibilities within the greening process through training and education.In the first phase of the presented project the status quo of company's organisational structureand culture to implement environmental management will be analysed; a strength/weaknessprofile participation and qualification of employees in the company specific will be conduced; aframework for an extended training program for the employees will be developed and multiplicator and actor group defined qualification steps (modules) will be developed andimplemented. On the end of this phase the participating company should be able through anincreased level of participation and qualification of their employees to improve theirenvironmental management system successfully by their own.The second phase will measure the progress of the initial qualification and participation steps. As a consequence of the upcoming results the modules will be optimised to guarantee a long-term participation of all employees involved (as long as the continuous improvement of theenvironmental management system is ongoing). In the third phase the specific results from the company-level (micro-level) are evaluated,extracted and transformed onto the sector level and documented in guidelines (handbook).The project focuses on small and medium sized companies in sectors that are especially affectedby the ecological-economical structural changes and where the potential of unemploymentoccurs. The consumer good industry is such an example. As well as in the furniture- and as in the food sector the number of people employed is decreasing. Therefore the partners of thisproject are 5-7 small to medium sized businesses of the furniture and food branch, whichadditionally have passed the EMAS requirements.The project is composed as a European transfer project, which permits comparison, andanalysis of business oriented environmental protection measures within the premises of EMASand promotes information transfer between the international participants.The results of the project will support the participating businesses to implement environmentalmanagement system, contribute to the consolidation of jobs and as a result improve the situationof employees within the branches.
urn:nbn:de:bsz:wup4-opus-7235
Keywords: 330